Preparation of polyoxometalate stabilized gold nanoparticles and composite assembly with graphene oxide: enhanced electrocatalytic performance. (14th December 2015) - Suo, Lin; Gao, Wenmei; Du, Yu; Wang, Ruiqiang; Wu, Lixin; Bi, Lihua
Abstract : P5 W30 stabilized Au nanoparticles and graphene oxide were fabricated to form composite films exhibiting good electrocatalytic activity for H2 O2 reduction. Abstract : Novel polyoxometalate stabilized gold nanoparticles (Au NPs) were prepared by a one-pot procedure in water at room temperature using Pressler-type tungstophosphate (NH4 )14 [NaP5 W30 O110 ]·31H2 O (P5 W30 ) as both a reducing and a stabilizing agent. The formation of P5 W30 stabilized Au NPs (Au@P5 W30 NPs) was verified by a comprehensive characterization involving UV-vis spectroscopy, IR spectroscopy, X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDX), X-ray diffraction analysis (XRD), dynamic light scattering (DLS) and zeta potential analysis. Afterwards, the composite films of (PDDA/Au@P5 W30 /PDDA/GO)8 (PDDA: polydimethyldiallyl ammonium chloride; GO: graphene oxide) comprising Au@P5 W30 NPs and GO were constructed on ITO-coated glass electrodes and quartz substrates based on a layer-by-layer (LBL) assembly. For comparison purposes, another three composite films of (PDDA/P5 W30 )8, (PDDA/Au@P5 W30 )8 and (PDDA/P5 W30 /PDDA/GO)8 were also fabricated simultaneously on ITO-coated glass electrodes using the same fabrication method. The effects of the composition of four composite films on the electrocatalysis of H2 O2 reduction were investigated. The results indicated that the tri-component composite film of (PDDA/Au@P5 W30 /PDDA/GO)8 shows enhanced electrocatalytic activity towards the reduction of H2 O2 due to the synergistic effect of tri-component Au NPs, P5 W30 and GO, large number of active sites and good electron conducting ability originating from GO and the Au NPs.